Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Answer:
x=7
Step-by-step explanation:
Let's solve your equation step-by-step.
5x+3−2x=24
Step 1: Simplify both sides of the equation.
5x+3−2x=24
5x+3+−2x=24
(5x+−2x)+(3)=24(Combine Like Terms)
3x+3=24
3x+3=24
Step 2: Subtract 3 from both sides.
3x+3−3=24−3
3x=21
Step 3: Divide both sides by 3.
Answer: x=7
Step-by-step explanation:
Given
5x + 3 - 2x = 24
Subtract both sides by 3
5x + 3 - 3 - 2x = 24 - 3
5x - 2x = 21
Simplify
3x = 21
Divide both sides by 3
3x / 3 = 21 / 3
x=7
Hope this helps!!
Please let me know if you have any questions
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.